Accounting Treatment of Damaged Products in UMKM Production Cost Calculation: Perlakuan Akuntansi atas Produk Rusak dalam Perhitungan Biaya Produksi UMKM - Putri Maulidiah Khasanah; Sarwenda Biduri (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Accurate cost accounting is essential for small enterprises to determine reliable production costs and financial reports. Specific Background: Many rural UMKM still rely on simple daily cash records without following the accounting cycle, including in handling damaged products during production. Knowledge Gap: Limited understanding of proper accounting treatment for damaged goods causes miscalculation of cost of production and reduces the reliability of financial information for external use. Aim: This study examines how damaged products are treated in calculating the cost of production at Pia Karomah UMKM in Kampung Pia, Pasuruan. Results: Findings show that financial records are manual and limited to income–expense notes, damaged products are not recorded according to cost accounting procedures, and production costs are calculated only from visible expenses. Novelty: The study links damaged-product accounting practices with rural UMKM financial literacy within a village-based production center. Implications: Strengthening accounting knowledge through training and guidance is necessary to improve cost calculation accuracy and financial reporting practices among village UMKM.